DataSheet1_Yedoma Permafrost Genesis: Over 150 Years of Mystery and Controversy.docx - Yuri Shur; Daniel Fortier; M. Torre Jorgenson; Mikhail Kanevskiy; Lutz Schirrmeister; Jens Strauss; Alexander Vasiliev; Melissa Ward Jones (2022)
Since the discovery of frozen megafauna carcasses in Northern Siberia and Alaska in the early 1800s, the Yedoma phenomenon has attracted many Arctic explorers and scientists. Exposed along coastal and riverbank bluffs, Yedoma often appears as large masses of ice with some inclusions of sediment. The ground ice particularly mystified geologists and geographers, and they considered sediment within Yedoma exposures to be a secondary and unimportant component. Numerous scientists around the world tried to explain the origin of Yedoma for decades, even though some of them had never seen Yedoma in the field. The origin of massive ice in Yedoma has been attributed to buried surface ice (glaciers, snow, lake ice, and icings), intrusive ice (open system pingo), and finally to ice wedges. Proponents of the last hypothesis found it difficult to explain a vertical extent of ice wedges, which in some cases exceeds 40 m. It took over 150 years of intense debates to understand the process of ice-wedge formation occurring simultaneously (syngenetically) with soil deposition and permafrost aggregation. This understanding was based on observations of the contemporary formation of syngenetic permafrost with ice wedges on the floodplains of Arctic rivers. It initially was concluded that Yedoma was a floodplain deposit, and it took several decades of debates to understand that Yedoma is of polygenetic origin. In this paper, we discuss the history of Yedoma studies from the early 19th century until the 1980s—the period when the main hypotheses of Yedoma origin were debated and developed.